Emotions and social relationships for breast and gynecologic patients: a qualitative study of coping with recurrence. Issue 4 (14th October 2013) - Thornton, Lisa M.; Levin, Anna O.; Dorfman, Caroline S.; Godiwala, Neha; Heitzmann, Carolyn; Andersen, Barbara L.
Abstract Background In contrast to the large literature on patients' coping with an initial diagnosis of cancer, there have been few quantitative or qualitative studies of patients coping with recurrence. A qualitative study was undertaken to aid in the development of a tailored intervention for these patients. Methods Individuals (N=35) receiving follow‐up care for recurrent breast or gynecologic cancer at a university‐affiliated cancer center participated in an individual or a group interview. Transcripts of interviews were analyzed using a coding format with two areas of emphasis. First, we focused on patients' emotions, as there is specificity between emotions and the corresponding ways in which individuals choose to manage them. Secondly, we considered the patients' social environments and relationships, as they too appear key in the adjustment to, and survival from, cancer. Results Patients identified notable differences in their responses to an initial diagnosis of cancer and their current ones to recurrence, including the following: (i) depressive symptoms being problematic; (ii) with the passing years and the women's own aging, there is shrinkage in the size of social networks; and (iii) additional losses come from social support erosion, arising from a) intentional distancing by social contacts, b) friends and family not understanding that cancer recurrence is a chronic illness, and/or c) patients stemming their support requests across time. Conclusion The contribution of these findings to the selection of intervention strategies is discussed. Copyright © 2013 John Wiley & Sons, Ltd.